(untitled) (Ho Chi Minh City, Viet Nam, 1996)
The book content the discussions the state of the art in the development and aplication od anaerobic technologies, and the strategies bof promotion of anaerobic technologies, and the concept for inter-regional exchange of information on anaerobic technologies.
Keywords: Environmental protection,Bảo vệ môi trường